Effect of temperature on the life cycle and predatory capacity of ladybird beetle Micraspis discolor Fabricius (Coleoptera: Coccinellidae) - Hong, Bui Minh; Thanh Binh, Tran Thi; Thu Hang, Vu Thi (Academia Journal of Biology, 2013)
The effects of temperature on the development and the predatory capacity of Micraspis discolor larvae were studied in laboratory. Two temperature levels 23.50°C and 30.71oC on average, were used to assess the life cycle and developmental stages of the ladybird beetle M. discolor. The life cycle of M. discolor was 27.38 days at 23.50°C and reduced to 19.77 days at 30.71°C, the total larval period was 13.42 and 9.9 days, respectively. The pre-oviposition period of the ladybird beetle M. discolor was 4.95 days at 23.50°C and 5.23 days at 30.71°C. The female beetles laid 282 eggs and the hatching percentage of egg was 81.03 at 30.71°C and 179 eggs and the hatching percentage of egg was 88.73 at 23.50°C. At temperature 30.71°C and 23.50°C, the pupal periods were 4.91 and 2.92 days, respectively. The longevity of adult ladybird beetles was slightly prolonged when they were reared at 30.71°C compared with that when they were reared at 23.50°C. Feeding on the second insturs of B. brassicae the predatory capacity of M. discolor larvae consumed an average 206.28 prey per day at 30.71°C and 161.84 prey per day at 23.50°C.